(N-Benzyl-N-isopropyldithiocarbamato)-chloridodiphenyltin(IV) - Abdul Muthalib, Amirah Faizah; Baba, Ibrahim; Mohamed Tahir, Mohamed Ibrahim; Seik, Weng Ng; Tiekink, Edward R. T. (International Union of Crystallography, 2010)
The SnIV atom in the title organotin dithiocarbamate, [Sn(C6H5)2(C11H14NS2)Cl], is penta-coordinated by an asymmetrically coordinating dithiocarbamate ligand, a Cl and two ispo-C atoms of the Sn-bound phenyl groups. The resulting C2ClS2 donor set defines a coordination geometry intermediate between square-pyramidal and trigonal-bipyramidal with a slight tendency towards the latter. The formation of close intramolecular C–H[cdots, three dots, centered]Cl and C–H[cdots, three dots, centered]S contacts precludes the Cl and S atoms from forming significant intermolecular contacts. The presence of C–H[cdots, three dots, centered]π contacts leads to the formation of supramolecular arrays that stack along the b axis.